The sensory channel of presentation alters subjective ratings and autonomic responses toward disgusting stimuli—Blood pressure, heart rate and skin conductance in response to visual, auditory, haptic and olfactory presented disgusting stimuli - Croy, Ilona; Laqua, Kerstin; Suess, Frank; Joraschky, Peter; Ziemssen, Tjalf; Hummel, Thomas (Frontiers in Human Neuroscience, 2013)
Disgust causes specific reaction patterns, observable in mimic responses and body reactions. Most research on disgust deals with visual stimuli. However, pictures may cause another disgust experience than sounds, odors or tactile stimuli. Therefore disgust experience evoked by four different sensory channels was compared. A total of 119 participants received 3 different disgusting and one control stimulus, each presented through the visual, auditory, tactile and olfactory channel. Ratings of evoked disgust as well as responses of the autonomic nervous system (heart rate, skin conductance level, systolic blood pressure) were recorded and the effect of stimulus labeling and of repeated presentation was analyzed. Ratings suggested that disgust could be evoked through all senses; they were highest for visual stimuli. However, autonomic reaction towards disgusting stimuli differed according to the channel of presentation. In contrast to the other, olfactory disgust stimuli provoked a strong decrease of systolic blood pressure. Additionally, labeling enhanced disgust ratings and autonomic reaction for olfactory and tactile, but not for visual and auditory stimuli. Repeated presentation indicated that participant’s disgust rating diminishes to all but olfactory disgust stimuli. Taken together we argue that the sensory channel through which a disgust reaction is evoked matters.